1978
DOI: 10.1128/aac.14.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibilities of Anaerobic Bacteria to Metronidazole, Ornidazole, and SC-28538

Abstract: The susceptibilities of 284 anaerobic bacteria, including 55 strains of the Bacteroides fragilis group, were determined by an agar dilution technique to metronidazole and two newer nitroimidazoles, ornidazole and SC-28538. All three agents showed marked in vitro activity against virtually all anaerobic bacteria tested. At concentrations c1 ,ig/ml, SC-28538 was significantly more active than either rnetronidazole or ornidazole. At concentrations of >1 ,ig/ml, the activities of all three agents were comparable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…For example, these agents were inactive against at least 25% of the Our results with clindamycin and metronidazole generally agree with those reported by other investigators (11,22,28,29 The new beta-lactam antibiotic, N-formimidoyl thienamycin, showed impressive in vitro activity against anaerobic bacteria. The overall inhibitory activity of this new compound was somewhat better than that of clindamycin and comparable to that of metronidazole.…”
Section: Resultssupporting
confidence: 91%
“…For example, these agents were inactive against at least 25% of the Our results with clindamycin and metronidazole generally agree with those reported by other investigators (11,22,28,29 The new beta-lactam antibiotic, N-formimidoyl thienamycin, showed impressive in vitro activity against anaerobic bacteria. The overall inhibitory activity of this new compound was somewhat better than that of clindamycin and comparable to that of metronidazole.…”
Section: Resultssupporting
confidence: 91%
“…The poor activity of metronidazole against gram-positive, nonsporeforming bacilli agrees with published reports (9,22 …”
Section: (13)supporting
confidence: 92%
“…to metronidazole (3,12,14) , cefoxitin (3,4,19), and clindamycin (4,5,8) has been shown. Metronidazole is generally ineffective on the other nonsporulated, gram-positive rods, contrasting with the good activity of cefoxitin and clindamycin; even some Propionibacterium spp.…”
mentioning
confidence: 99%